A Review Of G Code, STEP, STEP-NC, And Open Architecture Control Technologies Based Embedded CNC Systems - Latif, Kamran; Adam, Anbia; Yusof, Yusri; Abdul Kadir, Aini Zuhra (Springer Science and Business Media Deutschland GmbH, 2021)
Computer Numeric Control (CNC) is a significant pillar of manufacturing for decades. These systems are an essential part of future manufacturing. In the urge towards the development of next-generation manufacturing systems, various technologies have been introduced. Moreover, based on those technologies, numerous systems have been developed all around the world. In order to assist in future research, the related major technologies and developments are discussed in this content. This paper presents the review of basics CN), Computer-Aided Design (CAD), Computer-Aided Process Planning (CAPP), Computer-Aided Manufacturing (CAM), G codes (ISO 6983), Standard for the Exchange of Product (STEP) model data (STEP), STEP-numeric control (STEP-NC), and open architecture control (OAC) technologies. The in-depth discussion on the development and implementation of the STEP and STEP-NC technologies is also addressed. The review also highlights the benefits and role of the open architecture control technology in the CNC system development. Apart from that, the paper also presents the last 17 years of embedded CNC systems development in tabular form, which shows the cocktail of various technologies and ISO data interface models. Finally, the paper concludes with future directions and recommendations